An Evaluation of the Physician Retention Program in Newfoundland and Labrador - Young, Gillian F (Scholarship@Western, 2023)
Did physician retention bonuses improve retention in Newfoundland and Labrador (NL)? Data from the Medical Practice Registry from the Newfoundland and Labrador Department of Health and the Canadian Institute for Health Information (CIHI) were analyzed to 1) describe the physicians who work in NL, 2) examine physician length of practice (retention) in a community, and 3) examine community level retention. 1701 physicians who worked in NL between 2000 and 2015 were included in the study. We conducted ARIMA analyses to assess the effectiveness of the retention bonus programs and found no significant impact of the 2003 retention bonus. We found a significant increase in physician retention for specialists in Category 2 communities and a decrease in Category 3 communities following the 2009 retention bonus. Retention bonuses in NL did not improve physician- or community-level retention. Study findings suggest that resources could be better invested in other supports to increase physician retention.